2007
DOI: 10.1179/174328407x213242
|View full text |Cite
|
Sign up to set email alerts
|

Deformation twinning in AISI 316L austenitic stainless steel: Role of strain and strain path

Abstract: AISI 316L austenitic stainless steel was deformed at different strain and strain paths. The twin boundaries in the deformed microstructure had two possible origins: decay of original annealing twins and generation of deformation twins. Assuming that rotations of grains, specifically grains on both sides of a twin boundary, are responsible for the twin decay, a simple model was proposed to bring out the domain of relative twin generation. A biaxial strain path, in general, was associated with strong twin genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…These were confirmed by X-ray diffraction (valid for higher martensite percentages) and VSM (vibrating sample magnetometer)[34].…”
supporting
confidence: 56%
See 3 more Smart Citations
“…These were confirmed by X-ray diffraction (valid for higher martensite percentages) and VSM (vibrating sample magnetometer)[34].…”
supporting
confidence: 56%
“…This was attempted using both constant and varying r and n. A few interesting past studies can be cited [31][32], where varying r and n (from actual mechanical test data) were used successfully for improved FLC predictions. Past studies [34][35][36] have also shown a strong correlation between microstructure with strain and strain path. However, what makes the present study interesting is that it could convert tangible aspects of microstructural developments (e.g.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This can be explained in terms of larger grain size and/ or presence of softer second phase. Larger grain size is expected [48][49][50] to promote deformation twinning, though recent studies on twinning in single phase Zircaloy 2 [46,47] showed that f1 0 1 2gh1 0 1 1i tensile twins are affected more by crystallographic orientation than by moderate (similar as in the case of the present study) differences in-grain size. Twinning is also expected if slip is restricted [47,51,52].…”
Section: Deformation Twinningmentioning
confidence: 40%